Answer:
No.
Step-by-step explanation:
6^2=36
12^2=144
36/144 simplified is 1/4
If a2 -2ab + b2 = 9 and a![\begin{gathered} a^2-2ab+b^2=9 \\ aStep 1 factorize[tex]\begin{gathered} a^2-2ab+b^2=(a-b)^2 \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20a%5E2-2ab%2Bb%5E2%3D9%20%5C%5C%20a%3C%2Fp%3E%3Cp%3E%EF%BB%BFStep%201%20%3C%2Fp%3E%3Cp%3Efactorize%3C%2Fp%3E%5Btex%5D%5Cbegin%7Bgathered%7D%20a%5E2-2ab%2Bb%5E2%3D%28a-b%29%5E2%20%5C%5C%20%20%5Cend%7Bgathered%7D)
then
[tex]\begin{gathered} (a-b)^2=9 \\ \sqrt{(a-b)^2}=\sqrt{9} \\ a-b=\pm3 \\ \\ aa-b=-3
Answer: It’s 1
Explanation: it’s 1
Answer:
75%
Step-by-step explanation: